Analysis and Research on the Rehabilitation Effect of Physical Exercise on College Students’ Mental Depression Based on Multidimensional Data Mining - Wen Zou (Occupational Therapy International)
In order to explore the physical exercise and psychological changes of college students, this study adopts the method of multidimensional data mining, taking 23,146 undergraduates from a university in Guangzhou, Guangdong Province, as the research object. On the basis of summarizing and analyzing the previous research literature, this study expounds the development background, current situation, and future challenges of multidimensional data mining technology. This paper introduces the methods and principles of sample selection and multidimensional assessment of the physical and mental depression of college students, analyzes the physical health status of college students, summarizes the psychological changes of college students before and after the intervention, and discusses the relationship between physical exercise and mental health of college students. In addition, this paper analyzes the influencing factors and psychological changes of college students’ physical exercise and puts forward suggestions for improving the physical and mental health of college students. The results of this study show that with increasing age, college students have a lower risk of moderate anxiety and mild depression; girls are more prone to mild depression than boys; rural college students are more prone to mild, moderate anxiety; college students with nonmedical backgrounds were more likely to experience moderate anxiety than college students with medical backgrounds. During the intervention control period, continuous connection with others may encourage college students to actively use internal resources to actively cope with obstacles and setbacks, and as a protective factor, psychological resilience can appropriately weaken the association between risk factors in life and anxiety and relieve anxiety. The results of this study can provide a reference for further research on the physical exercise and psychological changes of college students.